Economic costs of biological invasions in the United States - Fantle-Lepczyk, Jean E; Haubrock, Phillip J; Kramer, Andrew M; Cuthbert, Ross N; Turbelin, Anna J; Crystal-Ornelas, Robert; Diagne, Christophe; Courchamp, Franck (The Science of the total environment, 2022)
The United States has thousands of invasive species, representing a sizable, but unknown burden to the national economy. Given the potential economic repercussions of invasive species, quantifying these costs is of paramount importance both for national economies and invasion management. Here, we used a novel global database of invasion costs (InvaCost) to quantify the overall costs of invasive species in the United States across spatiotemporal, taxonomic, and socioeconomic scales. From 1960 to 2020, reported invasion costs totaled $4.52 trillion (USD 2017). Considering only observed, highly reliable costs, this total cost reached $1.22 trillion with an average annual cost of $19.94 billion/year. These costs increased from $2.00 billion annually between 1960 and 1969 to $21.08 billion annually between 2010 and 2020. Most costs (73%) were related to resource damages and losses ($896.22 billion), as opposed to management expenditures ($46.54 billion). Moreover, the majority of costs were reported from invaders from terrestrial habitats ($643.51 billion, 53%) and agriculture was the most impacted sector ($509.55 billion). From a taxonomic perspective, mammals ($234.71 billion) and insects ($126.42 billion) were the taxonomic groups responsible for the greatest costs. Considering the apparent rising costs of invasions, coupled with increasing numbers of invasive species and the current lack of cost information for most known invaders, our findings provide critical information for policymakers and managers.
Keywords: Animals; náklady na zdravotní péči; zemědělství; Cost of Illness; Socioeconomic damages; Spojené státy americké; hmyz; Invasive alien species; zavlečené druhy; Nonindigenous species; United States; InvaCost; ekosystém; Ecosystem; zvířata; Introduced Species; Health Care Costs; osobní újma zaviněná nemocí; Non-native species; Insecta; Agriculture